The democratic transition after 2003 and its impact on the Iraqi media between freedom of expression and political exploitation - Saleh, Imad Mohammed (The International and Political Journal, 2026)
The research aimed to reveal the democratic transition after the year 2003 and its impact on the Iraqi media between freedom of expression and political employment, and the importance of the research comes from the fact that it addresses the media transformation in Iraq after 2003, as one of the most important indications of the democratic transition, as it sheds light on the contradiction between the provisions of the constitution that guarantee freedom of expression and the actual reality that witnesses a large political and partisan interference in the work of the media, and the researcher followed the descriptive analytical approach due to its appropriateness For the requirements of the research, the research has been divided into three comprehensive topics in addition to the introduction and conclusion containing the most prominent results and recommendations, and the researcher has reached several results, most notably that the Iraqi media has shifted from a media governed by controls and laws to a chaotic media that reflected the political chaos in Iraq, and the laws that governed the Iraqi media have evolved from the Ottoman Publications Law, and most of the Iraqi media are characterized by being affiliated with one of the religious and political bodies and lacked the media profession, and the Iraqi media has witnessed a great development after He occupied Iraq after these means were numbered and became private property after they were the monopoly of successive governments that ruled Iraq.